Corrigendum: Sustainable housing development in China: does financial institutions overcome the risks and challenges to sustainable housing? - Ma, Shaodong (Technological and Economic Development of Economy, 2024)
Shaodong Ma, author of the article “Sustainable housing development in China: does financial institutions overcome the risks and challenges to sustainable housing?”, published in Technological and Economic Development of Economy, 30(3), 627–645, https://doi.org/10.3846/tede.2024.20581 informs that in the article, pp. 627–630, some references were not strongly related to the content, and required refinement. The corresponding references needed to be removed from the list of references in pp. 640–642. This has now been corrected. The author regrets the errors.